2018 IEEE Integrated STEM Education Conference (ISEC) 2018
DOI: 10.1109/isecon.2018.8340510
|View full text |Cite
|
Sign up to set email alerts
|

People Like Me: Providing relatable and realistic role models for underrepresented minorities in STEM to increase their motivation and likelihood of success

Abstract: Despite efforts to increase participation of racial and ethnic minorities (excluding Asians) in science, technology, engineering and mathematics (STEM) in the United States, this group remains underrepresented in these fields. Many efforts to increase minority participation focus on support structures to help this group "get through" the pipeline. However, less attention has been paid to increasing their intrinsic motivation to pursue careers in STEM. Our work is focused on increasing this intrinsic motivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 7 publications
1
32
0
Order By: Relevance
“…We then surveyed potential role models (university alumni who themselves are URMs in STEM, based on evidence that race-and gender-matched role models may be more effective [6][7][8][9]) and created role model profiles that inherently highlighted the aforementioned qualities. Ultimately, we found that students viewed the individuals presented in these profiles as apt to serve as role models, confirming the effectiveness of our methodology [10].…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…We then surveyed potential role models (university alumni who themselves are URMs in STEM, based on evidence that race-and gender-matched role models may be more effective [6][7][8][9]) and created role model profiles that inherently highlighted the aforementioned qualities. Ultimately, we found that students viewed the individuals presented in these profiles as apt to serve as role models, confirming the effectiveness of our methodology [10].…”
Section: Introductionsupporting
confidence: 74%
“…Survey response data were input into the tool in a spreadsheet format with the headings and extraneous text deleted. The survey response data have been described in detail in previous publications [5,10,13] and will only be briefly summarized here for clarity. The role model case data includes 10 survey responses (10706 words total) from STEM alumni at a small, private liberal arts university, and the mentor case data includes 29 survey responses (26848 words total) from peer leaders in introductory STEM courses at a large, private research university.…”
Section: Methodsmentioning
confidence: 99%
“…al suggested [53], attempts to eliminate gender stereotypes from textbooks it is a good place to start to address the STEM aspiration gap of underrepresented groups like females. Existing literature [54]- [56] also agrees that exposing young females over time to people like them in instructional materials will increase their interest in STEM. An approach to tackle this issue in primary and secondary education is to work with stakeholdersparents, teachers, school leaders, publishers of educational materials and the government.…”
Section: Implications For Practicementioning
confidence: 88%
“…Unfortunately, minoritized students have been marginalized in STEM and within the STEM fields. In 2015, minoritized individuals comprised approximately 38% of the population in the USA (Anderson, 2015), but only made up about 12.7% of the total STEM workforce (Aish et al, 2018). Thus, it is imperative to disrupt the systems of oppression that are evident in our society to provide each and every student, including minoritized individuals, access to high-quality STEM experiences to develop STEM literacy, which is a critical asset needed by all in today's world.…”
Section: Introductionmentioning
confidence: 99%